Pengembangan Lms Moodle Dengan Model Problem Based Learning (PBL) Untuk Meningkatkan Hasil Belajar Pada Elemen Pemrograman Web (Studi Kasus: Murid Kelas XI TKJ SMK Negeri 1 Kediri) - Fathia Bilqish Wulandari; Rindu Puspita Wibawa (CV. SINAR HOWUHOWU, 2026)
The rapid advancement of digital technology demands that vocational education, particularly at the SMK level, produce graduates who are genuinely ready to meet workforce demands, especially in web programming. In practice, teaching the HTML-based web programming element still largely relies on conventional, one-way approaches, causing students to merely copy code without truly understanding the underlying structure and logic. This study aimed to describe the development and validation of a Moodle-based Learning Management System (LMS) adopting the Problem Based Learning (PBL) model, and to examine the extent to which students' learning outcomes in the web programming element changed following its implementation at SMK Negeri 1 Kediri. The LMS developed in this study was named Webnova. The development followed the Research and Development method using the ADDIE model, consisting of Analyze, Design, Development, Implementation, and Evaluation. Media expert assessment yielded a validity score of 90%, categorized as valid. Measurements using the User Experience Questionnaire (UEQ) showed that all six aspects (Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty) fell within the Good to Excellent range. The average posttest score reached 90.57, a substantial increase from the pretest score of 64.43, with a classical N-Gain value of 0.75 (high category). The Wilcoxon test produced a significance value of < 0.001 (< 0.05), confirming a meaningful difference before and after treatment. It can be concluded that the Webnova LMS, designed with the Problem Based Learning model, effectively improved the learning outcomes of grade XI TKJ 2 students at SMK Negeri 1 Kediri in the web programming element.